Cover Feature: Revealing the Flexible 1D Primary and Globular Secondary Structures of Sulfur‐Rich Amorphous Transition Metal Polysulfides (ChemNanoMat 12/2019). Issue 12 (22nd November 2019) - Artemkina, Sofya B.; Enyashin, Andrey N.; Poltarak, Anastassiia A.; Fedorenko, Anastasiya D.; Makarova, Anna A.; Poltarak, Pavel A.; Shin, Eon‐Ji; Hwang, Seong‐Ju; Kim, Sung‐Jin; Grayfer, Ekaterina D.; Fedorov, Vladimir E.
Abstract : Combined experimental and computational investigation shows that the exclusively amorphous nature of MoS5 and WS5 is related to flexible chains in their structures, akin to traditional polymers, making these materials remarkably different from most of the other transition metal chalcogenides that may be obtained in crystalline state. The presented findings are important for both fundamental understanding of possible formation processes of new materials and for promoting their practical uses, as shown on the example of Li‐ion batteries. More information can be found in the Full Paper by Sofya B. Artemkina, Andrey N. Enyashin, Ekaterina D. Grayfer et al. on page 1488 in Issue 12, 2019 (DOI: 10.1002/cnma.201900526 ).